2013
DOI: 10.1097/scs.0b013e318299775d
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Courses of Zygomaticofacial and Zygomaticotemporal Canals Using Micro-computed Tomography in Korean

Abstract: The zygomatic nerve (ZN), which originates from the maxillary nerve at the pterygopalatine fossa, enters the orbit through the inferior orbital fissure. Within the lateral region of the orbit, the ZN divides into the zygomaticofacial (ZF) and zygomaticotemporal (ZT) nerves. The ZF and ZT nerves then pass on to the face and temporal region through the zygomaticoorbital foramen and enter their own bony canals within the zygomatic bone. However, multiple zygomaticofacial and zygomaticotemporal canals (ZFCs and ZT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 16 publications
4
11
0
Order By: Relevance
“…The average number of foramina was 1.98 ± 0.93 in this African American population. While higher than previous studies, this is similar to results found in a recent micro-CT study of Koreans where an average of 2.2 foramina per zygomatic bone was reported 17 . While previous studies suggest no significant difference in the average number of zygomaticofacial foramina between right and left hemicrania, we found that the right side contained significantly more (2.13 ± 0.98) zygomatic foramina than the left side (1.68 ± 0.79) 12 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The average number of foramina was 1.98 ± 0.93 in this African American population. While higher than previous studies, this is similar to results found in a recent micro-CT study of Koreans where an average of 2.2 foramina per zygomatic bone was reported 17 . While previous studies suggest no significant difference in the average number of zygomaticofacial foramina between right and left hemicrania, we found that the right side contained significantly more (2.13 ± 0.98) zygomatic foramina than the left side (1.68 ± 0.79) 12 .…”
Section: Discussionsupporting
confidence: 90%
“…Methods of examining the zygoma include digital photographs and image analysis software, direct examination of the dry skull, and micro-CT 6, 9, 12 . Kim et al used micro-CT to assess number and the path of the foramen through the zygoma 17 . They compared their results to a previous study of Korean skulls examined in a similar manner to Mangal et al 9, 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The results of craniometric research of topographic anatomical peculiarities of zygomaticofacial foramina location on the facial surface of zygomatic bone turned out to be similar to the data of other authors regarding the variability of quantity and orderliness of zygomaticofacial foramina location [15][16][17][18][19][20]. There is great variability regarding the site of nerve division outside/inside the zygomatic bone and the number of foramina/canals, where nerves enter and leave the zygomatic bone [18].…”
Section: Discussionsupporting
confidence: 80%
“…Previous anatomical studies of the ZTF have revealed morphological features of the foramina on the lateral surface of the zygomatic bone [ 7 - 8 ]. Kim et al investigated the ZTF using micro-computed tomography (micro-CT) and found that the bony canal often bifurcates inside the zygomatic bone [ 9 ]. However, the bony canals identified in dry skulls or on CT could include not only the nerves but also vessels.…”
Section: Discussionmentioning
confidence: 99%